Implementation of Tax Collection on E-Commerce - Nizwatul Izzah; H.M. Galang Asmara; RR.Cahyowati (International Journal of Integrated Science and Technology, 2024)
The imposition of Income Tax (PPh) and Value Added Tax (VAT) in e-commerce transactions each has obstacles in its collection, one of which is caused by the current regulations which are deemed inadequate to maximize the potential for tax revenue from e-commerce transactions. The aim of carrying out this research is to find out and understand the regulations and application of taxes on e-commerce transactions in Mataram City, as well as the obstacles and efforts to overcome them. The results of research on the implementation of tax collection on e-commerce show that the tax on e-commerce transactions is considered to have not been realized optimally due to a lack of outreach to the public so that many e-commerce players do not understand e-commerce taxation. Apart from that, the tax collection system in the form of self-assessment makes the potential for negligence by taxpayers greater. The implementation of e-commerce PPh cannot yet run optimally because the government does not yet have a data tracking system to detect income obtained from e-commerce transactions. The advice given based on this conclusion is for the government to regulate sanctions for violations of e-commerce tax implementation so that repressive supervision can be carried out optimally. Apart from that, the government should collaborate with related institutions to minimize the potential for negligence by taxpayers.